Comprehensiveness of conservation of useful wild plants: An operational indicator for biodiversity and sustainable development targets - Khoury, Colin K.; Amariles, Daniel; Soto, Jonatan Stivens; Díaz, Maria Victoria; Sotelo, Steven; Sosa, Chrystian C.; Ramírez Villegas, Julián Armando; Achicanoy Estrella, Harold Armando; Velásquez Tibatá, Jorge; Guarino, Luigi; León, Blanca; Navarro Racines, Carlos Eduardo; et al. (Elsevier, 2019)
Plants are essential sources of food, medicine, shelter, fuel, feed, and forage, and provide a wide range of additional ecosystem and cultural services to humanity. In recognition of the tremendous value of useful plants and of the increasing threats to their persistence, international agreements including the Convention on Biological Diversity, the Sustainable Development Goals, and the International Treaty on Plant Genetic Resources for Food and Agriculture have created ambitious conservation targets which must be measured through quantitative indicators so as to facilitate the development and implementation of strategies aimed at safeguarding their genetic diversity. Gaps in the current list of functioning indicators for these targets suggest that the development of effective measurements of the state of conservation of the genetic diversity within useful plants is a major challenge. Here we present a gap analysis indicator methodology that provides a pragmatic estimate of the comprehensiveness of conservation of the genetic diversity within useful wild plants, both ex situ and in situ. The methodology compares the geographic and ecological variation evident from analyses of the ‘site of collection’ of samples of plant taxa that are safeguarded in genebanks and other living plant repositories, as well as the variation evident in the proportion of species’ ranges inhabiting protected areas, against the full range of geographic and ecological variation in their native distributions. The methodology enables a prioritization of species for immediate conservation action, and, when measured periodically, can quantify progress toward comprehensive conservation of these plants at global, regional, and national scales, including determining when that goal has been reached. Assessing almost 7000 taxa with the “Comprehensiveness of conservation of useful wild plants” indicator, we find that they are currently highly under-conserved, with less than three out of every 100 taxa assessed as sufficiently conserved or of low priority for further conservation action (overall global indicator = 2.78). Indicator results at the national and regional scales as well as by species use type varied, although virtually all countries, regions, and use categories were found to require further conservation action, particularly with regard to ex situ conservation. The results as well as input data and method code are available for indicator reporting and for conservation prioritization setting.